THE PREVALENCE OF INTESTINAL PARASITIC INFECTIONS AMONG PEDIATRIC PATIENTS IN KUT, IRAQ: A COMPARATIVE STUDY BY MEANS OF MICROSCOPY AND MULTIPLEX PCR - Abed, Rana Jaafer (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Intestinal parasitic infections (IPIs) continue as a substantial public health issue in evolving nations, with pediatric population’s presence particularly susceptible. This study examines the prevalence of Entamoeba histolytica, Giardia lamblia, and Cryptosporidium parvum among children in Kut, Iraq, using both conventional microscopy and Multiplex PCR methodologies. A total of 257 stool specimens were procured from children aged 0 to 14 years crossways various hospitals and healthcare institutions. The specimens underwent an initial macroscopic and microscopic evaluation, subsequently followed by DNA extraction and examination by Multiplex PCR to supplement the detection capabilities for parasitic pathogens. The collective infection rate was determined to be 42.41%, with a larger prevalence experiential in females (49.24%) when compared with males (35.20%). Age-group analysis indicated that children aged 12 to 14 years showed the highest infection rate (60.00%), while the lowest prevalence was renowned in children under three years of age (37.50%). A proportional analysis between urban and rural environments revealed a heightened infection prevalence in rural locales (55.17% vs. 41.18%). The diagnostic efficiency of microscopy and Multiplex PCR confirmed considerable concordance, with Pearson correlation coefficients above 0.99 for all three parasites, so representative a healthy contract between the two diagnostic approaches. Nevertheless, Multiplex PCR shown a slightly superior detection rate for Entamoeba histolytica, Giardia lamblia, and Cryptosporidium parvum. These results emphasize the authoritative for the addition of molecular diagnostic practices into standard clinical repetition to improve the sensitivity and accurateness of IPI detection, particularly within resource-constrained environments.